USER PREFERENCES IN IMAGE MAP USING - A. Vondráková; V. Vozenilek (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
In the process of map making, the attention is given to the resulting image map (to be accurate, readable, and suit the primary purpose) and its user aspects. Current cartography understands the user issues as all matters relating to user perception, map use and also user preferences. Most commercial cartographic production is strongly connected to economic circumstances. Companies are discovering user’s interests and market demands. However, is it sufficient to focus just on the user’s preferences? Recent research on user aspects at Palacký University Olomouc addresses a much wider scope of user aspects. The user’s preferences are very often distorting – the users think that the particular image map is kind, beautiful, and useful and they wants to buy it (or use it – it depends on the form of the map production). But when the same user gets the task to use practically this particular map (such as finding the shortest way), so the user concludes that initially preferred map is useless, and uses a map, that was worse evaluated according to his preferences. It is, therefore, necessary to evaluate not only the correctness of image maps and their aesthetics but also to assess the user perception and other user issues. For the accomplishment of such testing, eye-tracking technology is a useful tool. The research analysed how users read image maps, or if they prefer image maps over traditional maps. The eye tracking experiment on the comparison of the conventional and image map reading was conducted. The map readers were asked to solve few simple tasks with either conventional or image map. The readers’ choice of the map to solve the task was one of investigated aspect of user preferences. Results demonstrate that the user preferences and user needs are often quite different issues. The research outcomes show that it is crucial to implement map user testing into the cartographic production process.